2011
DOI: 10.1021/bi200049c
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-Bisphosphate Alters Synaptotagmin 1 Membrane Docking and Drives Opposing Bilayers Closer Together

Abstract: Synaptotagmin 1 (syt1) is a synaptic vesicle-anchored membrane protein that acts as the calcium sensor for the synchronous component of neuronal exocytosis. Using site-directed spin labeling, the position and membrane interactions of a fragment of syt1 containing its two C2 domains (syt1C2AB) were determined in bilayers containing phosphatidylcholine (PC), phosphatidylserine (PS) and phosphatidylinositol, 4,5-bisphosphate (PIP2). Addition of 1 mole% PIP2 to a lipid mixture of PC and PS results in a deeper memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
89
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 45 publications
11
89
0
Order By: Relevance
“…Given the close proximity of the lysine-rich cluster and the CBR, these results are compatible with a parallel orientation model (Fig. 6F) in which these two motifs would interact with a vesicle representing the plasma membrane, leaving the bottom face free to interact in trans with another lipid vesicle (19,(47)(48)(49)(50)(51). How these two C2 domains act in tandem and in cooperation with other SNARE proteins to regulate vesicle fusion is still under debate and will need further exploration.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Given the close proximity of the lysine-rich cluster and the CBR, these results are compatible with a parallel orientation model (Fig. 6F) in which these two motifs would interact with a vesicle representing the plasma membrane, leaving the bottom face free to interact in trans with another lipid vesicle (19,(47)(48)(49)(50)(51). How these two C2 domains act in tandem and in cooperation with other SNARE proteins to regulate vesicle fusion is still under debate and will need further exploration.…”
Section: Resultssupporting
confidence: 79%
“…Several studies have demonstrated that the C2B domain of syt1 induces Ca 2+ -dependent lipid aggregation as indicative of the predisposition to facilitate the fusion of synaptic membranes in cooperation with the SNARE complex (19,45,46). Critical Arg residues located at the polybasic region (Lys326/Lys327) and at the bottom face (Arg398/Arg399) of the domain are responsible for that function (19,45,47). To investigate if the reconstitution of the lysine-rich cluster in the C2A domain of synaptotagmin would participate in this process, we measured the ability of syt1 C2A, syt1 C2A-E194K, and syt1 C2B domains to induce vesicle clustering at increasing protein concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…For the C2D, C2E, and C2F domains, association rate constants remained similar at the different calcium concentrations, whereas the dissociation rate decreased significantly at 20 M calcium. min-1 and PIP 2 via positively charged synaptotagmin lysine residues is an important step in neuronal vesicle fusion (40), and it has been shown that PIP 2 enhances calcium binding by synaptotagmin-1 (28,41,42). Light scattering results indicate that under the conditions of the present investigation otoferlin C2 domain proteins are properly folded and non-aggregating (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…PIP2 is able to regulate many important cellular processes including vesicular trafficking, platelet activation, and organization of the cytoskeleton, 28,29,30 and it may control several steps in focal adhesion. 19,20,31 PIP2 can also affect protein conformation, 32,33,34,35 target cytoplasmic proteins to the membrane, and stabilize protein oligomers. 31,36 In this article, we focus on clarifying the importance of lipid membrane composition in the conformational modulation of integrins.…”
Section: Introductionmentioning
confidence: 99%